Star cursed - Spotswood, Jessica (Cahill witch chronicles, 2014)
Cate Cahill goes into an asylum in order to meet her godmother and another oracle as she continues to try to learn about the prophecy and protect her sisters from the oppressive Brotherhood in an alternate New England of 1900.